Determinants of adaptation practices to climate change: insights from soybean growers in Central India: DETERMINANTS OF PRACTICES TO CLIMATE CHANGE: INSIGHTS FROM SOYBEAN GROWERS IN INDIA - B U DUPARE; PURUSHOTTAM SHARMA; S D BILLORE (Journal of Oilseeds Research, 2021)
The study analyzed the determinants of adaptation practices of soybean growers toward climate change in Central India using primary data collected through household survey from 280 soybean growers. The influence of a set of explanatory variables on each of the different adaptation strategies was simultaneously modeled using multivariate probit analysis. The most widely practiced adaptation measure was change in the variety (71% farmers) followed by the change in time of farm operations and crop change or crop diversification. To cope with the insect-pest and disease attack on the crops, farmers adopted resistant varieties to minimize the cost of chemical spray. More than one-third of the sampled farmers practiced change in input application, while soil and water management practices were practiced by nearly 28% of the farmers. Analysis of results indicated that the change in varieties of crops is significantly more likely to be adopted by households with larger family size, higher involvement in extension activities, having a tractor, higher educated head of household. Households with higher family income, possessing mobile phones and other infrastructure are more likely to adopt the change in varieties, whereas farmers having highersocial participation, extension contact, larger land holding, and belonging to ethnic origin other than scheduled caste or scheduled tribe do not necessarily do so. The government should frame out policiestowardsthe promotion oftechnological and institutional measuressuitable to various categories offarmers so that the adaptation strategies could be helpful in maintaining and/or increasing the sustainability of the production systems.